Manajemen Perencanaan dan Pengorganisasian Pembelajaran Bahasa Arab - Silvia, Neng; Saepudin, Asep Ahmad; Mufidah, Nuril; Amrullah, Abdul Malik Karim (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2023)
The purpose of this study was to determine the management of planning and organizing Arabic language learning at Amal Jama'i Islamic Boarding Schools, as well as to determine the supporting and inhibiting factors in learning Arabic. The research method used in this study is a descriptive qualitative method. Data collection techniques were carried out by interviews and observations with descriptive data analysis techniques in accordance with Miles and Huberman's theory. The results of this study show that: 1) The planning management in learning Arabic is carried out by establishing Arabic learning programs, preparing learning materials, and determining relevant learning media, 2) The organizing management in learning Arabic begins with the division of teaching tasks, then the preparation of lesson schedules, as well as the provision of learning facilities, 3) Several supporting factors for learning Arabic include support from the headmaster of the college, the existence of a language division, and the stipulation of Arabic days of the week, while the inhibiting factors are inadequate time allocation, lack of human resources and environmental influences. The results of this study can be used as a reference for Arabic language activist researchers and academics.